1988
DOI: 10.1111/j.1476-5381.1988.tb11600.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term desensitization of guinea‐pig taenia caecum induced by carbachol occurs at intracellular Ca stores and that by histamine at H1‐receptors

Abstract: 1 In Ca-free solution, the contractile response of guinea-pig taenia caecum to 1O-'M carbachol was mediated through muscarinic receptors and was reduced time-dependently by desensitization with 1O-4M carbachol, but not 1O-4M histamine. On the other hand, the response to 1O-4M histamine was shown to be mediated through HI-receptors and to be reduced time-dependently by desensitization with either iO-4 M histamine or 10' M carbachol. 2 The maximal K+ contraction was not changed by desensitization with carbachol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
2

Year Published

1989
1989
2003
2003

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 16 publications
4
35
2
Order By: Relevance
“…It has been shown that histamine responses can be modulated in vivo (Manning et al, 1987) and in vitro. Histamine-induced desensitization of the H1-receptor has been documented in various isolated cell systems (Lewis Baenzinger et al, 1981;Brown et al, 1986;Nakahata & Harden, 1987;McDonough et al, 1988) and smooth muscle preparations (Anderson et al, 1979;Kenakin & Cook, 1979;Bielkiewicz & Cook, 1984;Hishinuma & Uchida, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that histamine responses can be modulated in vivo (Manning et al, 1987) and in vitro. Histamine-induced desensitization of the H1-receptor has been documented in various isolated cell systems (Lewis Baenzinger et al, 1981;Brown et al, 1986;Nakahata & Harden, 1987;McDonough et al, 1988) and smooth muscle preparations (Anderson et al, 1979;Kenakin & Cook, 1979;Bielkiewicz & Cook, 1984;Hishinuma & Uchida, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…That is, the K+-induced contraction was more rapid and the tonic tension was not maintained after treatment with carbachol as shown in Figure 1. On the other hand, there was no change in the K+-induced contractions in the histamine-induced desensitized state as shown in Figure 2 and in our previous paper (Hishinuma & Uchida, 1988 (a(i)). (b) (ii) Conditions were as in (a(ii)) except that 3 x 10-5M dibucaine was used instead of tetracaine.…”
Section: Resultsmentioning
confidence: 66%
“…We have been investigating muscarinic and histamine desensitization of smooth muscle contraction. We have found that contractions dependent on the release of intracellularly stored Ca elicited by carbachol, histamine and caffeine were heterologously desensitized by carbachol, while histamine homologously desensitized the histamine-elicited contraction (Hishinuma & Uchida, 1988). We concluded that desensitization induced by carbachol and histamine was due to the functional changes of intracellular Ca stores and histamine H,-receptors, respectively.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations